Sazonalidade, luminosidade e déficit hídrico sobre aspectos ecofisiológicos em Erythroxylum pauferrense. - Ribeiro, João Everthon da Silva (2020)
Seasonal variations of abiotic factors, such as irradiance and water availability, can influence the ecophysiology of understory species. In this context, this research was carried out with the objective of evaluating effects of the seasonal variation, luminosity and water availability on ecophysiological aspects in Erythroxylum pauferrense. In Article I, the objective was to evaluate the effects of seasonality on ecophysiological aspects of E. pauferrense in an open and closed canopy area. The research was carried out in the Mata do Pau-Ferro State Park, located in the municipality of Areia, Paraíba, Brazil. The readings were taken monthly in two periods of the year: dry (September 2017 to February 2018) and rainy (March to August 2018); and in two areas, A1 (open canopy) and A2 (closed canopy). The leaf area index, visible sky fraction and photosynthetically active radiation were measured in five individuals in the two areas. In each area, data of humidity and soil temperature, monthly precipitation and air temperature were also collected. Subsequently, the effects of these environmental variables on the variables of gas exchange, chlorophyll a fluorescence, leaf chlorophyll indices, morphofunctional attributes and water relations were analyzed. The data were submitted to multivariate analysis by means of canonical correlation analysis and principal component analysis to verify correlations between ecophysiological and environmental variables, subsequently to assess the differences between ecophysiological variables, the analysis of mixed effect variance with repeated measures over time, and then the means were grouped by the Scott-Knott test. E. pauferrense individuals respond to seasonal variations in A1 and A2, showing less ecophysiological development in the dry period. Seasonality influences the ecophysiological aspects of E. pauferrense in A1 and A2, with greater influence of soil moisture, precipitation and leaf area index in gas exchange, chlorophyll a fluorescence and chlorophyll indexes. In Article II, the objective was to evaluate morphophysiological aspects of E. pauferrense seedlings submitted to different levels of shading. The experiment was carried out at the Federal University of Paraíba, Campus II, Areia, Paraíba, Brazil, and conducted in a greenhouse in a completely randomized design, with five treatments: 0%, 30%, 50%, 70% and 90% shading, and eight repetitions. Growth characteristics, morphofunctional attributes, gas exchange, chlorophyll a fluorescence and chlorophyll indices were evaluated. The data were submitted to analysis of variance and polynomial regression. Plants submitted to shading of 30% have greater growth and physiological performance, which is the most recommended for the production of E. pauferrense seedlings. In Article III, the objective was to evaluate the morphophysiological characteristics of E. pauferrense plants submitted to water deficit. The research was carried out in a greenhouse, at the Federal University of Paraíba, Campus II, Areia, Paraíba, Brazil. The experimental design was in randomized blocks, with five water treatments [100%, 80%, 60%, 40% and 20% of the pot capacity (CP)], and four repetitions. The evaluated parameters were: growth, morphofunctional aspects, gas exchange, chlorophyll a fluorescence and leaf chlorophyll indices. The data were subjected to analysis of variance and in cases of significance, polynomial regression analyzes were performed. It was found that largest deficit (20% of CP) provided reductions in the parameters evaluated. The 80% CP regime is the most recommended for the production of E. pauferrense seedlings, promoting greater growth and significant changes in the morphofunctional aspects, gas exchange, chlorophyll a fluorescence and chlorophyll indexes.